Quantifying the benefits of peer support for people with dementia: A Social Return on Investment (SROI) study. (April 2018) - Willis, Elizabeth; Semple, Amy C; de Waal, Hugo
Objective: Peer support for people with dementia and carers is routinely advocated in national strategies and policy as a post-diagnostic intervention. However there is limited evidence to demonstrate the value these groups offer. This study looked at three dementia peer support groups in South London to evaluate what outcomes they produce and how much social value they create in relation to the cost of investment. Methods: A Social Return on Investment (SROI) analysis was undertaken, which involves collecting data on the inputs, outputs and outcomes of an intervention, which are put into a formula, the end result being a SROI ratio showing how much social value is created per £1 of investment. Results: Findings showed the three groups created social value ranging from £1.17 to £5.18 for every pound (£) of investment, dependent on the design and structure of the group. Key outcomes for people with dementia were mental stimulation and a reduction in loneliness and isolation. Carers reported a reduction in stress and burden of care. Volunteers cited an increased knowledge of dementia. Conclusions: This study has shown that peer groups for people with dementia produce a social value greater than the cost of investment which provides encouraging evidence for those looking to commission, invest, set up or evaluate peer support groups for people with dementia and carers. Beyond the SROI ratio, this study has shown these groups create beneficial outcomes not only for the group members but also more widely for their carers and the group volunteers.